KOMUNIKASI POLITIK TERKAIT HOAKS PADA PEMILU PRESIDEN INDONESIA 2024 - Juditha, Christiany (Jurnal Studi Komunikasi dan Media, 2024)
The spread of hoaxes through digital media, especially political ones, has become increasingly widespread, with 2,882 hoax content cases handled by Indonesia's Ministry of Communication and Digital in early 2024. Of these, 203 were election-related hoaxes. Hoaxes during elections are often used as propaganda to influence public opinion and election results. This research, using quantitative content analysis, aimed to examine political communication related to hoaxes in the 2024 Indonesian Presidential Election. The study found that misleading and manipulative hoaxes were used to attack political opponents, mostly through videos on YouTube and TikTok. Hoaxes involving Artificial Intelligence are also on the rise. Political hoaxes are often planned and executed by parties supporting or opposing specific candidates. The Prabowo-Gibran pair and President Jokowi were the main targets. Those spreading hoaxes are typically opponents of certain candidates and the current government. These hoaxes are designed to create hostility and harm political opponents, with strong political motives. Trusted fact-checking teams play a crucial role in helping the public avoid being misled by providing digital literacy on the truth of information.